Bilateral giant cell tumor of tendo Achilles: A case series on reconstruction by peroneus brevis - tibialis posterior tendon. (September 2021) - Mohapatra, Nirmal C.; Samal, Puspak; Mylarappa, Akshay; Mishra, Jitendra
Highlights: Bilateral GCT-TS of tendo Achilles is rare. GCT-TS of tendo Achilles destroys the tendon by progressive ischemia and local invasion. Excision of the tumor leaves a large defect. Satisfactory outcome of peroneus brevis - tibialis posterior tendon for tendo Achilles reconstruction. Abstract: Giant cell tumor of tendon sheath usually is localized painless solitary benign swelling, which presents as a firm nodular gradually growing mass. Giant cell tumor is infrequent in the lower limb and its incidence in the tendo Achilles is rare. It is often diagnosed and treated conservatively as tendinitis in the initial stages. The slow growth and limited functional deficit is the reason for its late presentation where excision of the mass leaves a large residual defect, for which reconstruction of the tendo Achilles has to be done by mobilizing different tendons. A case series of bilateral giant cell tumor of tendo Achilles and study the functional outcome of the reconstructed tendo Achilles using peroneus brevis - tibialis posterior tendons - are presented. The outcome of reconstruction using peroneus brevis - tibialis posterior tendon gave satisfactory outcome at the end of one year. Level of evidence: Level 4.